10 Seizoenen Kunst op de Borg. - Centrum Beeldende Kunst, Groningen; Bosch, Petra (Groningen : Centrum Beeldende Kunst, 1987)
Aapkes, Franklin ; Blaauw, Gjalt ; Bos, Egbert J. ; Brouwer, Jan ; Belmonte, Candida Colaço ; Dijkers, Ruud ; De Fluiter, Adri ; Gerbenzon, Nico ; Hamersma, Gerlof ; Nieuwlaat, Frans ; Oelen, Henk ; Oskam, Johan ; Otten, Els ; Popma, Carola ; Schmier, Marie-Louise
bibliografie
biografie
10 Seizoenen Kunst op de Borg, Centrum Beeldende Kunst, Groningen, 1987
Nederlands
boek